Risk Score Based on Critical Factors Associated with COVID-19 - Martínez-Peláez, Rafael; García, Vicente; Ayala Herrera, José Luís; Rivera Enrique, Solange Ivette; Sánchez Ruíz, Abraham; Córdova Albore, Liliana Carolina (2020)
The rapid spread of COVID-19 among Mexican population has had a great impact on the rates of infected people and the daily confirmed deaths by the new coronavirus. As a consequence, the public and private sector response was self-isolation and keep the strategy called "jornada de sana distancia" along two months. However, Mexican government declared that on June 1st the reopening of the country and economy will be conducted gradually; this means that many people will come back to their workplace. This paper proposes a new method to evaluate the risk to be infected by COVID-19, using the people mobility and the presence of some comorbidities.